2021
DOI: 10.1186/s12913-020-06014-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of systems dynamics and group model building to identify barriers and facilitators to acute care delivery in a resource limited setting

Abstract: Background Group model building (GMB) is a method to facilitate shared understanding of structures and relationships that determine system behaviors. This project aimed to determine the feasibility of GMB in a resource-limited setting and to use GMB to describe key barriers and facilitators to effective acute care delivery at a tertiary care hospital in Malawi. Methods Over 1 week, trained facilitators led three GMB sessions with two groups of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A strength of process mapping itself is its ability to showcase the timing in which a barrier arises during a process and the steps that both precede and follow that barrier. Process mapping is complementary to “group model building” (GMB), a system dynamics-based method in which contributors develop a causal loop diagram that models problems and opportunities for improvement ( 22 , 60 ). The identification of barriers through process mapping can help inform GMB and causal loop diagrams, which in turn will further improving tailoring of implementation strategies to match determinants ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strength of process mapping itself is its ability to showcase the timing in which a barrier arises during a process and the steps that both precede and follow that barrier. Process mapping is complementary to “group model building” (GMB), a system dynamics-based method in which contributors develop a causal loop diagram that models problems and opportunities for improvement ( 22 , 60 ). The identification of barriers through process mapping can help inform GMB and causal loop diagrams, which in turn will further improving tailoring of implementation strategies to match determinants ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review found that families identified barriers in the form of: (1) structural barriers (e.g., wait times, cost); (2) individual-level barriers including (a) family attitudes towards treatment; (b) limited family knowledge of mental health problems and how to seek and access help; and (c) family circumstances such as a family's support network (27). In another study that asked parents about barriers to seeking outpatient services for their children, 60.3% reported lack of information about where to seek help as a barrier, 59.8% reported professionals not listening as a barrier, and 53.7% reported providers not initiating treatment or issuing referrals as a barrier (28). While past research highlights the depth of knowledge that parents hold regarding their experience seeking services for their children, no prior studies have examined the unique process families go through to access EBIs for anxiety and OCD, including the timeline and barriers involved in accessing treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In these regard, attempts were made to construct reliable assumptions from local experts. In any new situation, the required data are not collected initially and the only option available is to use local experts which is common practice 35. The immediate solution is to rapidly replace the real data as it becomes available and use an iterative process to derive at the best estimate.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative group model building (GMB) and key informant interviews were used to identify opportunities for the Midwest SUPper Club to effectively leverage their collective expertise to advance outcomes for people with perinatal SUD. GMB is a community-based applied systems thinking methodology to elicit systems structures, stakeholder mental models, 2 and insights about how to meaningfully improve system behavior (Hovmand, 2014 ; Muttalib et al, 2021 ; Sterman, 2000 ). GMB differs from other stakeholder engagement methods in its use of facilitated, scripted activities to apply evidence-based components of systems thinking, as well as its strong emphasis on exploring potential positive and negative short- and longer-term impacts of policy and intervention options (Hovmand et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%